Energy absorption analysis of density graded aluminum foam - Li, Jingde (2012)
A numerical approach is carried out to investigate the energy absorption efficiency of density graded aluminium foam. Effects of blast load impact velocity, loading duration and sample thickness on the input energy density and output energy density of the graded foam are investigated. The stochastic meso-scale aluminium foam structure is generated by adopting a 2D Voronoi technique and the commercial software ANSYS/LS-DYNA is used for the FE modelling. Parametric study shows that the density graded aluminium foam is effective in improving energy absorption capability while keeping a lower stress transmitted to the substrate or the protected structure if it is properly designed.